FIGHTING THE CLOCK: A LITERATURE-BASED ANALYSIS OF MELATONIN’S THERAPEUTIC ROLE IN SHIFT WORK-RELATED SLEEP DISTURBANCES - Kacper Jankowski; Anna Daniel; Natalia Kraciuk; Alicja Bury; Karol Bartecki; Julia Błoniecka; Małgorzata Piekarska-Kasperska; Katarzyna Krupa; Jan Kamiński (International Journal of Innovative Technologies in Social Science, 2025)
Shift Work Sleep Disorder (SWSD) arises from misalignment between endogenous circadian rhythms and irregular work schedules, frequently resulting in poor sleep quality, increased fatigue, and heightened risk for cardiometabolic complications. Melatonin, a hormone produced in the pineal gland during darkness, is increasingly investigated for its role in addressing sleep difficulties among shift workers. This review synthesizes recent clinical evidence on the effectiveness of melatonin supplementation in improving sleep outcomes in night and rotating shift populations. The literature indicates potential benefits such as shorter sleep onset latency, increased total sleep time, and improved subjective sleep quality, alongside a strong safety record. Furthermore, melatonin’s influence on circadian rhythm regulation may provide additional metabolic and cardiovascular advantages. Nevertheless, inconsistencies in dosing, formulations, and trial designs limit the generalizability of current findings. Additional well-controlled clinical trials are needed to refine guidelines for melatonin use in occupational settings.